Asthma as a comorbidity in COVID‐19 pediatric ICU admissions in a large metropolitan children's hospital. Issue 1 (2nd November 2022) - Schroeder, Jonathan C.; Sharron, Matthew P.; Wai, Kitman; Pillai, Dinesh K.; Rastogi, Deepa
Abstract: Rationale: Children contribute to 5% of coronavirus disease of 2019 (COVID‐19)‐related hospitalizations in the United States. There is mounting evidence suggesting childhood asthma is a risk factor for severe disease. We hypothesized that asthma is associated with longer length of stay (LOS) and need for respiratory support among children admitted to pediatric intensive care unit (PICU) with COVID‐19. Methods: We reviewed 150 charts of children and young adults with a positive severe acute respiratory syndrome coronavirus 2polymerase chain reaction test admitted to the PICU at Children's National Hospital, Washington, DC between 2020 and 2021. We recorded demographics, anthropometrics, past medical history, clinical course, laboratory findings, imaging, medication usage, respiratory support, and outcomes. Functional Status Scale (FSS), which measures an Intensive Care Unitpatient's physical function, was used to characterize children with multiple comorbidities; FSS and obesity were included as covariates in multivariate analysis. Statistical analysis was performed using SPSS v25.0. Results: Sixty‐Eight patients ages 0–21 years met inclusion criteria. Median age was 14.9 years, 55.9% were female, median Body Mass Index percentile was 62, and 42.6% were African American. Compared with those without asthma, patients with asthma averaged longer LOS (20.7 vs. 10.2 days, p = 0.02), with longer PICU stay (15.9 vs. 7.6 days, p = 0.033) and prolonged maximum respiratory support (8.3 vs. 3.3 days, p = 0.016). Adjusted for obesity and poor physical function (FSS > 6), asthma remained a significant predictor of hospital LOS, PICU LOS, and days on maximum respiratory support. Conclusion: Asthma can cause severe disease with prolonged need for maximum respiratory support among children with COVID‐19.